The Identification of Long Non-coding RNA H19 Target and Its Function in Chronic Myeloid Leukemia - Juhua Yang; Zhao Yin; Yumin Li; Yanjun Liu; Guiping Huang; Chunming Gu; Jia Fei (Elsevier, 2020)
H19 is a long non-coding RNA which was lowly expressed in chronic myeloid leukemia (CML). Here, we found that the overexpression of H19 significantly inhibited cell viability and colony formation and prolongs survival in CML cell lines and three xenografted mouse models. The H19 target proteins and microRNAs (miRNAs) were identified using a combination of computational prediction and RNA pull-down, including PCBP1, FUS protein, and miR-19a-3p and miR-106b-5p. Targeting PCBP1, FUS protein, miR-19a-3p, and miR-106b-5p significantly inhibits the cell growth and colony formation of CML cell lines. Co-overexpression of H19 and PCBP1, FUS, miR-19a-3p, and miR-106b-5p decreases the inhibitory effect of H19 in CML. These findings might provide a novel molecular insight into CML. Keywords: long non-coding RNA, H19, CML, target identification, transcription in vitro, RNA pull-down assays, mass spectrometry, bioinformatics prediction, antisense